The evolving image of the German Democratic republic as reflected in the works of Jurek Becker and Christa Wolf - Williams, Alison Elizabeth (Rhodes University, Faculty of Humanities, School of Languages, 2009)
The primary objective of this thesis is to demonstrate the direct relationship between history and literature, with particular reference to literature published in the German Democratic Republic. It explores the period of history from 1945 to 1990 describing the collapse of National Socialist Germany after World War Two; the formation of the Federal Republic of Germany in the West and the German Democratic Republic in the East in 1949; the historical, political and cultural evolution of East Germany until the fall of the Berlin Wall in November 1989, and finally the absorption of the German Democratic Republic into the Federal Republic of Germany in 1990.
Keywords: Becker, Jurek, 1937-1997; Wolf, Christa; German fiction -- Germany (East) -- 20th Century; Germany (East) -- History -- 20th Century; Germany (East) In literature